COMPLEX OF METHODICAL MEANS OF FORMATION OF ECOLOGICAL AND LEGAL COMPETENCE OF UNIVERSITY STUDENTS IN THE PROCESS OF NATURAL SCIENCES EDUCATION - Sergey B. Ignatov (Obrazovanie i Nauka, 2015)
The aim of the investigation is to present the ways and a technique of formation of students’ ecological and legal competence at humanities departments of high schools in the course of studying of natural sciences. Methods and results. Having applied the methods of pedagogical modelling and using resources of natural-science disciplines, the author has developed a new complex based on structure and maintenance of the methodical tools that is directed at ecological and legal competence of high school students.Substantial block of the complex includes the integrated training course «Modern scientific picture of the world», supporting elective courses and interdisciplinary modules of eco-cultural orientation. Implementing ideas and cognitive models of postnonclassical science (systems theory, self-organization and organization) enables to provide an approach to describe the natural sciences and the social and cultural world with unified methodological positions, to build a complete system-synergetic picture in which the life of animate and inanimate nature, human life and work and society are inseparable single thread. The general laws of self-organization and evolution of complicated systems taught in the basic course enable to identify the similarities and differences in the dynamics of natural and social processes, face the problem of ecological culture and ethical and legal mechanisms, to regulate human activity that enhances deontological content of natural science training.The technology block of the educational complex includes technology and teaching methods, which combine traditional and innovative forms of the organization of educational process. «Case studies» technology is proposed as a productive tool for developing ecological and legal competence. This technology successfully integrates many of the current well-known methods and forms of education, promoting the implementation of the competency approach.Scientific novelty and practical significance. The results of the diagnostic research presented in the paper show that the use of the proposed educational complex enriches the eco-cultural knowledge of students, contributes to encouraging them to master natural science area, and is an effective tool in formation of ecological and legal competence. Testing the complex in the training process among different categories of students gives grounds to conclude that it can be wider used in educational practice.